Air lime-earth blended mortars - Assessment on fresh state and workability - Faria, Paulina (2016)
International Conference on Vernacular Heritage, Sustainability and Earthen Architecture, VerSus 2014, 2nd MEDITERRA, 2nd ResTAPIA, 11-13 September, Valencia, Spain